Short interfering RNA against STAT1 attenuates cisplatin-induced ototoxicity in the rat by suppressing inflammation - Kaur, T (Nature Publishing Group, 2011)
Cisplatin is widely used for treating various solid tumors. However, this drug produces dose-limiting ototoxicity and nephrotoxicity, which significantly reduce the quality of life of cancer patients. While nephrotoxicity could be alleviated by diuresis, there is currently no approved treatment for hearing loss. Previous studies show that the ROS and inflammation are major contributors to cisplatin-induced hearing loss. In this study, we show that ROS trigger the inflammatory process in the cochlea by activating signal transducer and activator of transcription-1 (STAT1). Activation of STAT1 activation was dependent on ROS generation through NOX3 NADPH oxidase, knockdown of which by siRNA reduced STAT1 activation. Moreover, STAT1 siRNA protected against activation of p53, reduced apoptosis, reduced damage to OHCs and preserved hearing in rats. STAT1 siRNA attenuated the increase in inflammatory mediators, such as TNF-α, inhibition of which protected cells from cisplatin-mediated apoptosis. Finally, we showed that trans-tympanic administration of etanercept, a TNF-α antagonist, protected against OHC damage and cisplatin-induced hearing loss. These studies suggest that controlling inflammation by inhibition of STAT1-dependent pathways in the cochlea could serve as an effective approach to treat cisplatin ototoxicity and improve the overall quality of life for cancer patients.